Kekayaan Jenis Ikan Elasmobranchii di TPI Bajomulyo Kabupaten Pati dan Status Konservasinya - Setiati, Ning; Putri, Khoirinida Suftiyani (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
The wealth of marine biota species in Indonesia are very diverse, both from bony fish and cartilaginous fish (Elasmobranchii). The Elasmobranchii fish are currently facing an extinction rate problem due to overfishing. Based on the IUCN Red List, 1 shark species is classified as Critically Endangered, 5 shark species are Endangered, 23 sharks species are Vulnerable and 35 other sharks species are in Near Threatened in Indonesia. The research aims to identify, describe the type and conservation status of Elasmobranchii fish caught at TPI Bajomulyo. The research method uses observation and interview techniques. Data were collected from March to April 2020. The determination of the type was analyzed descriptively based on the results of the observed assessment characteristics. The determination of the conservation status used in this research include the International Union for Conservation of Nature (IUCN), Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), Indonesian Government Regulation Number 8 Year 1999, Constitution Number 5 Year 1990 and Ministerial Regulation of Environment and Forestry Number P.106 Year 2018. There are 11 species of Elasmobranchii fish found during the research process. These species include Carcharhinus sealei (NT), Chiloscyllium punctatum (NT), Dasyatis kuhlii (DD), Himantura gerrardi (VU), Himantura undulata (VU), Himantura jenkinsii (VU), Pastinachus sephen (NT), Taeniura meyeni (VU), Gymnura poecilura (NT), Rhynchobatus australiae (CR), and Rhina ancylostoma (CR). Based on CITES, there are only 2 species categorized as Appendix II, Rhynchobatus australiae and Rhina ancylostoma. This research provides benefits for fisherman and related agencies to pay attention to catching protected fish so that it is sustainability is maintained.